Lost in Interpretation : Why Spouses Disagree on Who Makes Decisions - Liaqat, Sundas; Donald, Aletheia; Jarvis, Forest; Perova, Elizaveta; Johnson, Hillary C. (World Bank, Washington, DC, 2021)
Across a wide variety of regions and contexts, surveys have found high rates of disagreement within couples on matters of household decision making. Using a unique data set from a spousal survey of 421 agricultural households in the Philippines, this paper finds that 50.2 percent of couples disagree about who makes any given decision in the household. The paper systematically explores the empirical relevance of theoretical explanations from the existing literature for this spousal disagreement. Spouses are no more likely to agree on specific decisions compared with general decision making, are more likely to agree on the decision-making process, and are less likely to agree on decision making for activities in which both take part. Moreover, women are more likely to report that their husbands were involved in decision making when speaking with a female enumerator. The findings suggest that intrahousehold disagreement is not driven by differing interpretations of which decisions count as “major,” or by asymmetric information. Although the paper finds evidence of enumerator effects, their magnitude is small and cannot explain the observed rates of spousal disagreement over decision making. Rather, spousal disagreement appears to stem primarily from systematic gender differences in interpreting what it means to be a decision maker. The paper discusses the implications of the findings for the measurement of intrahousehold decision making in household surveys.